2022
DOI: 10.1111/bph.15783
|View full text |Cite
|
Sign up to set email alerts
|

l‐Citrulline ameliorates pathophysiology in a rat model of superimposed preeclampsia

Abstract: Background and Purpose Preeclampsia, characterized by hypertension, proteinuria and restriction of fetal growth, is one of the leading causes of maternal and perinatal mortality. So far, there is no effective pharmacological therapy for preeclampsia. The present study was conducted to investigate the effects of supplementation with l‐citrulline in Dahl salt‐sensitive rats, a model of superimposed preeclampsia. Experimental Approach Parental Dahl salt‐sensitive rats were treated with l‐citrulline (2.5 g·L−1 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 92 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…Our results are in line with previous studies demonstrating citrulline efficiency against hypertension in different animal models. The 0.25% of citrulline given in drinking water during 8 weeks decreased MBP in spontaneously hypertensive rats [ 35 ] and dahl salt-sensitive rats [ 52 ]. Here, we demonstrated that, in normotensive rats, citrulline prevents MBP increase induced by IH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in line with previous studies demonstrating citrulline efficiency against hypertension in different animal models. The 0.25% of citrulline given in drinking water during 8 weeks decreased MBP in spontaneously hypertensive rats [ 35 ] and dahl salt-sensitive rats [ 52 ]. Here, we demonstrated that, in normotensive rats, citrulline prevents MBP increase induced by IH.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by a decrease in eNOS activity triggered by ADMA production and/or by a decrease in arginine availability due to an increase in arginase activity as previously described under IH [ 30 , 63 ]. Regarding citrulline protective mechanisms, it was demonstrated to impact eNOS dynamics by increasing the total eNOS protein expression, S1177 phosphorylation, and NO production [ 52 , 64 ]. However, in the small pulmonary arteries of piglets, the vasorelaxation induced by citrulline was maintained in the presence of N(G)-Nitro-L-arginine methyl ester (L-NAME), this indicates that other factors than eNOS can explain the beneficial impact of citrulline on vascular tone [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Man et al have revealed that citrulline attenuates the progression of pre‐eclampsia by suppressing the NF‐κB pathway. 33 In addition, Ba et al have identified that citrulline inhibits ferroptosis in the thymus via inactivating the NF‐κB pathway. 34 Herein, we predicted that citrulline could combine with p65.…”
Section: Discussionmentioning
confidence: 99%
“…The NF‐κB pathway may be the underlying mechanism of citrulline function. For example, Man et al have revealed that citrulline attenuates the progression of pre‐eclampsia by suppressing the NF‐κB pathway 33 . In addition, Ba et al have identified that citrulline inhibits ferroptosis in the thymus via inactivating the NF‐κB pathway 34 .…”
Section: Discussionmentioning
confidence: 99%